Volterra runge- kutta methods for solving nonlinear volterra integral equations - Mustafa, Muna Mansur (Baghdad Science Journal., 2010)
في هذا البحث طرق فولتيرا رانجا–كوتا التي تتضمن طرق من الرتبة الثانية و الرابعة طبقت على معادلات فولتيرا التكاملية اللاخطية من الرتبة الثانية. فضلا عن ذلك تمت دراسة تقارب خوارزميات طرق فولتيرا رانجا–كوتا. و أخيرا كتبت البرامج الخاصة بكل طريقة باستخدام لغة الماتلاب و تم إجراء مقارنة بين الطرق باستخدام الأخطاء التربيعية. In this paper Valera Runge-Kutta methods which include : method of order two and four will be applied to general nonlinear Valera integral equations of the second kind. Moreover we study the convergent of the algorithms of Valera Runge-Kutta methods. Finally, programs for each method are written in MATLAB language and a comparison between the two types has been made depending on the least square errors.